The effectiveness of Problem-Based Learning (PBL) model in increasing students' cognitive outcomes and learning motivation in Environmental Change Material - Gusman, Hardina Briliyani; Rachmawati, Rivanna Citraning; Ulfah, Maria; Priyatna, R. Edy (Universitas Wiralodra, 2023)
The results of observations at SMA N 10 Semarang, teachers have tried to increase student motivation and learning outcomes by providing assignments and digital-based learning media but the there are still not optimal. The implementation of teacher learning still uses a lot of the conventional learning model. Students consider biology lessons to be just a collection of concepts that must be memorized. Students still do not associate much learning material with phenomena that exist in the surrounding environment. The effect is students are less motivated in learning the material. The purpose of this study was to determine the effectiveness of the Problem Based Learning model in improving cognitive outcomes and student motivation in environmental change material. The research method used in this research is pre-experimental one group pretest-postets. The population used in this study were all students of class X.10 SMA N 10 Semarang with a total of 37 students. The conclusion of the results of this study shows that the Problem Based Learning model has a high category of effectiveness in increasing cognitive outcomes and student learning motivation.